ANTIOXIDANT OF n-HEXANE EXTRACT OF Uncaria gambir RoxbFROM PONTIANAK: ANTIOKSIDAN EKSTRAK n-HEXANE Uncaria Gambir Roxb DARIPONTIANAK - Susana; Dodi Iskandar (ROCE : Jurnal Pertanian Terapan, 2025)
The n-hexane extract of dried UGR leaves was obtained with a yield of 8.0 grams (16%). Phytochemicalscreening revealed the presence of secondary metabolites, including phenolics, steroids, and terpenes.The antioxidant activity was evaluated using the DPPH assay, yielding an IC50 value of 53.654 ppm,which classified the extract as strong, falling within the 50–100 ppm range. However, n-hexane extractsgenerally exhibit weaker antioxidant activity due to the nonpolar nature of the solvent, which limits theextraction of polar antioxidant compounds such as polyphenols and flavonoids. Consequently, n-hexane extracts contain higher amounts of lipids, terpenes, and other nonpolar compounds, which are less effective at scavenging DPPH radicals compared to polar extracts like ethanol or methanol.